Ответ:
[tex]8) \: \sqrt{22}.[/tex]
[tex]9) \: 5.[/tex]
Объяснение:
[tex]8) \: \displaystyle2 \sqrt{5 \frac{1}{2} } + \frac{1}{3} \sqrt{99} - 2 \sqrt{2 \frac{3}{4} } = 2 \sqrt{ \frac{11}{2} } + \frac{1}{3} \sqrt{99} - 2 \sqrt{ \frac{11}{4} } = (\sqrt{2} ) {}^{2} \times \frac{ \sqrt{11} }{ \sqrt{2} } + \frac{1}{3} \times 3 \sqrt{11} - 2 \times \frac{ \sqrt{11} }{2} = \sqrt{22} + \sqrt{11} - \sqrt{11} = \sqrt{22} .[/tex]
[tex] \displaystyle9) \: \frac{19}{ \sqrt{20} + 1 } + 6 - 2 \sqrt{5} = \frac{19}{2 \sqrt{5} + 1} + 6 - 2 \sqrt{5} = \frac{19(2 \sqrt{5} - 1)}{(2 \sqrt{5} + 1)(2 \sqrt{5} - 1)} + 6 - 2 \sqrt{5} = \frac{ 19(2 \sqrt{5} - 1) }{4 \times 5 - 1} + 6 - 2 \sqrt{5} = \frac{19(2 \sqrt{5} - 1) }{19} + 6 - 2 \sqrt{5} = 2 \sqrt{5 } - 1 + 6 - 2 \sqrt{5} = 5.[/tex]
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
[tex]8) \: \sqrt{22}.[/tex]
[tex]9) \: 5.[/tex]
Объяснение:
[tex]8) \: \displaystyle2 \sqrt{5 \frac{1}{2} } + \frac{1}{3} \sqrt{99} - 2 \sqrt{2 \frac{3}{4} } = 2 \sqrt{ \frac{11}{2} } + \frac{1}{3} \sqrt{99} - 2 \sqrt{ \frac{11}{4} } = (\sqrt{2} ) {}^{2} \times \frac{ \sqrt{11} }{ \sqrt{2} } + \frac{1}{3} \times 3 \sqrt{11} - 2 \times \frac{ \sqrt{11} }{2} = \sqrt{22} + \sqrt{11} - \sqrt{11} = \sqrt{22} .[/tex]
[tex] \displaystyle9) \: \frac{19}{ \sqrt{20} + 1 } + 6 - 2 \sqrt{5} = \frac{19}{2 \sqrt{5} + 1} + 6 - 2 \sqrt{5} = \frac{19(2 \sqrt{5} - 1)}{(2 \sqrt{5} + 1)(2 \sqrt{5} - 1)} + 6 - 2 \sqrt{5} = \frac{ 19(2 \sqrt{5} - 1) }{4 \times 5 - 1} + 6 - 2 \sqrt{5} = \frac{19(2 \sqrt{5} - 1) }{19} + 6 - 2 \sqrt{5} = 2 \sqrt{5 } - 1 + 6 - 2 \sqrt{5} = 5.[/tex]